Multiple DAG off-line task scheduling for heterogeneous networked automobile electronic systems - Guo-qi XIE; Ren-fa LI; Fan YANG; Wei-hong HUANG (Tongxin xuebao)
Fairness and communication overhead have become the major bottleneck in performance of scheduling,a fair sorting criteria based on round-robin with communication overhead weight was proposed and a selection criteria based on assigning the task to the minimum selection value considering insertion was proposed in processor selection phase.The multiple DAG off-line and fairness task scheduling(MDOFTS)algorithm was proposed combining the above two phases to reduce the schedule length and communication overhead.Heterogeneous networked automobile electronic systems are typical mixed-criticality embedded systems,which must make sure to be real-time and to reduce scheduling length.The multiple DAG off-line and priority task scheduling (MDOPTS) algorithm was proposed to make sure the safety-critical DAG.The multiple DAG off-line and adaptive task scheduling(MDOATS)algorithm was proposed to improve the system performance on the basis of real-time based on MDOFTS and MDOPTS.Example analysis and experimental results show that the MDOFTS algorithm is better than other algorithms in schedule length,communication overh unfairness,worst-case response time and real-time.